2024
DOI: 10.1093/sysbio/syae009
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Predictors of Organelle Genome Evolution: Phylogenetic Correlations with Taxonomically Broad, Sparse, Unsystematized Data

Konstantinos Giannakis,
Luke Richards,
Iain G Johnston

Abstract: Comparative analysis of variables across phylogenetically linked observations can reveal mechanisms and insights in evolutionary biology. As the taxonomic breadth of the sample of interest increases, challenges of data sparsity, poor phylogenetic resolution, and complicated evolutionary dynamics emerge. Here, we investigate a cross-eukaryotic question where all these problems exist: which organismal ecology features are correlated with gene retention in mitochondrial and chloroplast DNA (organelle DNA or oDNA)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…We found that the same features of hydrophobicity, GC content, and energetic centrality predict cpDNA gene retention as well as mtDNA retention -and, strikingly, this prediction is quantitative in the sense that a model trained on mtDNA retention profiles predicts cpDNA retention profiles (Giannakis, Arrowsmith, et al, 2022). The theory developed suggesting that strong and dynamic environmental demands favour organelle gene retention also applies to cpDNA (García-Pascual et al, 2022), and we observed consistencies among environmental features statistically linked with gene retention profiles in both organelles (Giannakis et al, 2024). Indeed, a weak but robust correlation between mtDNA and cpDNA gene counts is detectable in the subset of species for which records are available for both (Giannakis, Richards, et al, 2023).…”
Section: Across Eukaryotes -Across Organelles?supporting
confidence: 53%
See 3 more Smart Citations
“…We found that the same features of hydrophobicity, GC content, and energetic centrality predict cpDNA gene retention as well as mtDNA retention -and, strikingly, this prediction is quantitative in the sense that a model trained on mtDNA retention profiles predicts cpDNA retention profiles (Giannakis, Arrowsmith, et al, 2022). The theory developed suggesting that strong and dynamic environmental demands favour organelle gene retention also applies to cpDNA (García-Pascual et al, 2022), and we observed consistencies among environmental features statistically linked with gene retention profiles in both organelles (Giannakis et al, 2024). Indeed, a weak but robust correlation between mtDNA and cpDNA gene counts is detectable in the subset of species for which records are available for both (Giannakis, Richards, et al, 2023).…”
Section: Across Eukaryotes -Across Organelles?supporting
confidence: 53%
“…This theory predicts semi-quantitatively that more oDNA encoding is advantageous in organisms subject to strong, variable environmental demands, while nuclear transfer is advantageous in stable, less demanding environments. This is supported by a cross-taxa phylogenetic comparative investigation of mtDNA gene count and ecology (Giannakis et al, 2024). Here, attempting to account for the difficulty of comparisons across the broad, sparse, uncertain datasets available, we found fewer genes retained in organelles exposed to limited demands (endoparasites, and plastids without photosynthetic demands) and more genes in those exposed to more varying environments (in sessile organisms, deserts, and tropical oceans).…”
Section: Properties Of a Species Favouring Retention Of More Genesmentioning
confidence: 60%
See 2 more Smart Citations
“…The retained subset of genes in organelles and endosymbionts varies dramatically across eukaryotes, and the features favouring gene retention are not completely understood (Butenko et al, 2024;García-Pascual et al, 2022;Giannakis et al, 2023Giannakis et al, , 2024McCutcheon & Moran, 2012;Smith & Keeling, 2015). Hypotheses have often focused on mitochondria and plastids, and have included roles for hydrophobicity (making it harder for nuclear-encoded genes to be imported to the organelle (Björkholm et al, 2015;von Heijne, 1986)); favouring local individual control of organelles (colocalization for redox regulation or CoRR (Allen, 2015)); the economics of maintaining and expressing genes from diFerent compartments (Kelly, 2021), and others (quantitatively compared in (Giannakis et al, 2022)).…”
Section: Introductionmentioning
confidence: 99%